Jesień życia pracowników nauki. Codzienność i kontakty społeczne emerytowanych nauczycieli akademickich uczelni krakowskich - Kapralska, Łucja; Maksymowicz, Agata (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2025)
The work concerns the ways of experiencing old age by a socio-professional group, such as retired scientists, and is based on in-depth interviews conducted among 12 retired scientists from Krakow. The aim of the research was to present the organisation of their everyday life, hobbies, interests and social relationships with others, considered by researchers to be the basis for successful ageing. The results indicate that retirement provides respondents with satisfaction due to a leisurely lifestyle and freedom from duties. The dominant focus is on family, relationships with friends, hobbies and non-stereotypical ways of spending free time. The most popular activity of Polish retirees, which is watching television, is not indicated by the respondents. What distinguishes senior scientists from other retirees is maintaining their social role in life, both by delaying retirement and by undertaking, to some extent, tasks related to this role also during it. This attitude fits into the theory of active ageing/role continuation and allows us to think optimistically about the quality of the autumn of life of the surveyed seniors.